Micranthes petiolaris variety shealyi: A New Variety of Micranthes (Section Stellares, Saxifragaceae) from South Carolina - Cushman, Laary J.; Richards, Vincent P.; Mcmillan, Patrick D. (Phytotaxa, 2020)
A new variety of Micranthes is described from a low-elevation granite outcrop in Pickens County, South Carolina. It is similar to high elevation Micranthes petiolaris populations in leaf morphology and chloroplast DNA (cpDNA) sequences, but differs in its annual habit, floral morphology, phenology, and ecology. The variety is known only from the type locality, with most clusters of individuals occurring along the forested boundary of an open granite outcrop, associated with Juniperus virginiana L., and growing upon moist to saturated moss mats and/or shallow soils. A discussion comparing the proposed taxon with M. petiolaris is provided, with notes about the distribution, habitat, and taxonomy of the variety.